Constituent elements of prohibited vertical agreements in the competition law of Iran and the European Union - Nezhad, Hedayatollah Soltani; Hazeri, Javad (Cuestiones Políticas, 2020)
The objective of the investigation is to analyze the constituent elements of vertical agreements prohibited by Iran's competition law, in accordance with Chapter IX of the Law on the Implementation of General Policies and in accordance with Article 44 of the Constitution and, as set out in European Union competition law, Article 101 of the Treaty on the Functioning of the European Union. By vertical agreements it can be said that one of the types of agreements is wanted in the competition law. Any reference between natural or legal persons in the longitudinal direction (whether top to bottom or bottom up) that is not close to the consumer's interest is agreed. These agreements may include free clauses that are not compatible with the objectives of competition law. Methodologically, this is a documentary research close to comparative and legal hermeneutics. It is concluded that, to prohibit vertical agreements, they need to have the anti-competitive object or effect and also have a tangible impact on the closure of competition on the market.